POWER, PATRIMONY AND DEMOCRACY (Andamios, Revista de Investigación Social, 2009)
Based on a national, bureaucratic and subordinate capitalist state, the idea of patrimony, which guides quite a few of the policies and projects in cultural management in Mexico, is functional to hegemony and the market standards. This paper discusses that building democracy and an alternative nation involves analyzing the scope and potential of cultural management. The first step is deconstructing the category of patrimony itself, which in its complex historical articulation implies social, political and economical determinations, that often remain invisible and on the sidelines in the debates on the subject.-
Keywords: Cultural patrimony; fetishism of the merchandise; capitalism; hegemony; social construction of meaning; cultural and symbolic capital; value of use; aesthetic dimension